2012
DOI: 10.1007/s00213-011-2592-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled laboratory study of the effects of d-cycloserine on craving in cocaine-dependent individuals

Abstract: Rationale D-cycloserine (DCS), a partial glutamate NMDA receptor agonist, enhances extinction of conditioned fear responding; preliminary data suggests that it may facilitate extinction of drug cue reactivity. Objective This study investigates DCS effects on cocaine cue craving and drug use in cocaine-dependent subjects. Methods Thirty-two subjects were randomly assigned to receive 1) DCS only, 2) DCS before sessions 1 and 3, PBO before session 2 or 3) PBO only 15-min before each of 3 1-hour cocaine cue ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 26 publications
2
51
1
Order By: Relevance
“…Pharmacological treatment has been shown to enhance the utility of exposure therapy for patients with generalized anxiety disorder (51); however, little efficacy has been shown in addicted populations (52). In fact, some studies demonstrate increased cue-induced craving in patients treated with D-cycloserine, an NMDA receptor agonist (53, 54). Notably, the majority of these experiments used exposure that did not involve performance of the instrumental response to reduce craving.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological treatment has been shown to enhance the utility of exposure therapy for patients with generalized anxiety disorder (51); however, little efficacy has been shown in addicted populations (52). In fact, some studies demonstrate increased cue-induced craving in patients treated with D-cycloserine, an NMDA receptor agonist (53, 54). Notably, the majority of these experiments used exposure that did not involve performance of the instrumental response to reduce craving.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an important promise in the treatment of this disorder, which is so prevalent and difficult to handle. Cocaine craving is enhanced in cocaine seekers by D-cycloserine (507). There are similarities between craving behavior for different drugs, but the relation between the effects of D-cycloserine and those of pexacerfont, if any, is not even hinted at; the relation of both to fear learning is not known, although of course there is a strong component of anxiety and even fear in drug-deprived addicts (583,584).…”
Section: Corticotropin-releasing Factormentioning
confidence: 99%
“…Cue reactivity encompasses objective measures of sympathetic arousal and/or subjective reports of craving, induced by paraphernalia or pictures associated with the abused drug. These small proof-ofconcept trials have shown decreased cue reactivity for nicotine (Santa Ana et al, 2009), no effect compared with placebo for nicotine (Kamboj et al, 2012;Yoon et al, 2013) and alcohol (Kamboj et al, 2011;Watson et al, 2011), or increased cue reactivity for cocaine (Price et al, 2009(Price et al, , 2013 and alcohol (Hofmann et al, 2012). One study that investigated clinically meaningful outcomes of D-cycloserine for augmenting cueexposure therapy found negative results for nicotine use (Yoon et al, 2013).…”
mentioning
confidence: 99%